Enhanced Charge Collection in MOF‐525–PEDOT Nanotube Composites Enable Highly Sensitive Biosensing. Issue 11 (22nd September 2017) - Huang, Tzu‐Yen; Kung, Chung‐Wei; Liao, Yu‐Te; Kao, Sheng‐Yuan; Cheng, Mingshan; Chang, Ting‐Hsiang; Henzie, Joel; Alamri, Hatem R.; Alothman, Zeid A.; Yamauchi, Yusuke; Ho, Kuo‐Chuan; Wu, Kevin C.‐W.
Abstract: With the aim of a reliable biosensing exhibiting enhanced sensitivity and selectivity, this study demonstrates a dopamine (DA) sensor composed of conductive poly(3, 4‐ethylenedioxythiophene) nanotubes (PEDOT NTs) conformally coated with porphyrin‐based metal–organic framework nanocrystals (MOF‐525). The MOF‐525 serves as an electrocatalytic surface, while the PEDOT NTs act as a charge collector to rapidly transport the electron from MOF nanocrystals. Bundles of these particles form a conductive interpenetrating network film that together: (i) improves charge transport pathways between the MOF‐525 regions and (ii) increases the electrochemical active sites of the film. The electrocatalytic response is measured by cyclic voltammetry and differential pulse voltammetry techniques, where the linear concentration range of DA detection is estimated to be 2 × 10 −6 –270 × 10 −6 m and the detection limit is estimated to be 0.04 × 10 −6 m with high selectivity toward DA. Additionally, a real‐time determination of DA released from living rat pheochromocytoma cells is realized. The combination of MOF5‐25 and PEDOT NTs creates a new generation of porous electrodes for highly efficient electrochemical biosensing. Abstract : A novel nanocomposite consists of poly(3, 4‐ethylenedioxythiophene) nanotubes (PEDOT NTs) coated with porphyrin‐based metal–organic framework nanocrystals (MOF‐525) via in situ synthesis. The MOF‐525 serves as an electrocatalytic surface and the PEDOT NTs act as a charge collector to rapidly transport the electron from MOF nanocrystals. The obtained nanocomposites establish a new generation of porous electrodes for highly efficient electrochemical biosensing.